History of monitoring the endangered ivory gull in the Canadian Arctic - Mark L. Mallory; H. Grant Gilchrist (Arctic Science, 2024)
The ivory gull (Pagophila eburnea Phipps 1774) is a rare seabird found in the Canadian High Arctic. The Seymour Island Migratory Bird Sanctuary has supported the core colony for ivory gull research since the 1970s, but by the 2000s, survey work was extended across the species’ range in Nunavut, prompted by growing Indigenous concerns of population declines, which led to regular monitoring of colonies. We found marked declines in numbers of ivory gulls since the 1980s, especially in the southern part of the range, leading the Canadian Committee on the Status of Endangered Wildlife in Canada to recommend uplisting ivory gulls to Endangered under Canada’s Species At Risk Act, which the federal government did in 2009. This resulted in the development of a national Recovery Strategy that outlined research and monitoring needs. Canadian results prompted international concern and led to coordinated, international research and monitoring on this iconic Arctic species, which collectively suggested worldwide declines in the species’ numbers. Despite our efforts, the future of monitoring, and indeed of ivory gulls in Canada, remains unclear.